Taxonomy of the Proisotoma complex. II. A revision of the genus Subisotoma and a description of Isotopenola gen. nov. (Collembola: Isotomidae) - Potapov, Mikhail; Babenko, Anatoly; Fjellberg, Arne; Greenslade, Penelope (Zootaxa, 2009)
A taxonomic revision of the genus Subisotoma Stach, 1947 is presented. Subisotoma pusilla (Schäffer, 1900), S. tenuis (Dunger, 1982), and S. asiatica (Martynova, 1970) are re-described based on type and fresh material. Eight new species of the genus are described; S. pomorskii sp. nov., S. homonomica sp. nov., S. bisensillata sp. nov., S. guzeriplica sp. nov., S. posteriomollis sp. nov., S. multisensillata sp. nov., S. cruda sp. nov., and S. erratica sp. nov., using material from Eurasia. A key to the known species of Subisotoma is given.